2021
DOI: 10.21203/rs.3.rs-576429/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Country-Level Factors Dynamics and ABO/Rh Blood Groups Contribution To COVID-19 Mortality

Abstract: Identifying factors related to COVID-19 mortality is important to deploy effective containment measures and to safeguard categories at risk. In the last months, several investigations have tried to ascertain essential features for predicting the COVID-19 mortality tolls depending on country-specific dynamics and population structure. Most studies focused on the initial outbreak of COVID-19 spanning the first half of 2020. Several variables, including obesity, health system indicators such as hospital bed densi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The ABO and Rh systems, which play a fundamental role in transfusion medicine and hematopoietic transplantation, have been associated to the pathogenesis and pathophysiology of various human diseases, such as cardiovascular and oncological diseases, , and also have a role in the susceptibility to microorganism, viral, and parasitic infections. …”
Section: Introductionmentioning
confidence: 99%
“…The ABO and Rh systems, which play a fundamental role in transfusion medicine and hematopoietic transplantation, have been associated to the pathogenesis and pathophysiology of various human diseases, such as cardiovascular and oncological diseases, , and also have a role in the susceptibility to microorganism, viral, and parasitic infections. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, hemolytic disease of the newborn baby is a real concern when Rh is mismatched between mother and offspring [10]. Recently scientists concluded that the Rh blood type is associated with COVID-19 and Rh negative has a protective role [11]. Therefore, this work aims to investigate the association between the ABO blood group and susceptibility to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%